Laser Cladding In Situ Carbide-Reinforced Iron-Based Alloy Coating: A Review - Junli Tang; Kaiming Wang; Hanguang Fu (Metals)
Laser cladding, as an advanced surface modification technology, has the advantages of a high energy density, controlled dilution rate and good metallurgical bonding between the coating and the substrate. Its rapid heating and cooling properties help to form a dense and fine coating structure on the surface of the substrate, thus enhancing wear and corrosion resistance. In recent years, the in situ generation of carbide-reinforced iron-based composite coatings has gradually become a research hotspot because it combines the high hardness values of carbide with the high toughness values of iron-based alloys, which significantly improves the comprehensive performance of the coatings. This paper reviews the research progress of laser cladding in situ carbide-reinforced iron-based alloy coatings and explores the role of different types of in situ synthesized carbides (TiC, NbC, WC, etc.) in the coatings and their effects on their wear resistance and mechanical properties. The distribution of carbides in the coatings and their morphological characteristics are also discussed, and the effects of laser power, scanning speed and auxiliary treatments (ultrasonic vibration, induction heating, etc.) on the microstructure and properties of the coatings are analyzed. Finally, the problems and future directions of development in this field are envisioned.